Neurodivergent, Queer and/or Trans, Femme: can "Neurofemme" be (more than) theory? - Chatterjee, Sohini (Revista Mundaú, 2023)
Drawing on femme, neuroqueer, and neurotrans scholarship, as well as disability studies academic and disability justice activist literature, I explore political and subcultural possibilities that could be generated when queer and/or trans neurodivergent femmes—or “neurofemme”—positionality/positionalities are foregrounded as an epistemic, methodological, ethical, political, and sub/cultural necessity. Imbued with an anti-ableist, anti-sanist, anti-disablist, anti-caste, and anti-racist sense of equity—both structurally and in the everyday innermost spaces and realms—this article is a hopeful exercise in imagining the journey of “neurofemme” as a structural positionality as well as a political identity that can forge critical solidarities with variously oppressed femmes as well as historically excluded trans and/or queer people. “Neurofemme” recognizes that trans and/or queer femmes—whose homogeneity is actively sought by capitalist homonormative and transformative technologies of power—are also neurodivergent and that LGBT exceptionalism demands compulsory neurotypicality and relentless performance of neuronormativity. Neurofemme theory, by challenging sanist, ableist, and disablist demands placed on the bodyminds of variously marginalized neurofemmes, imagines equitable possibilities while wondering what political and sub/cultural effects and affects “neurofemme” could occasion and how neurofemme lives can be supported when the term is uttered with political and sub/cultural intentionality.